RELATIONSHIP BETWEEN HANDWASHING HABITS WITH DIARHEA INCIDENT IN CHILDREN UNDER TWO YEARS - Arini, Shintia Yunita; Pramesti, Nala Astari; Prasasti, Dian; Awwalina, Isas (Fakultas Kesehatan Masyarakat, Universitas Jember, 2021)
Diarrhea in children under five based on diagnosis and symptom occurred in 18.5% of children in 2018 and 12.3% of children in 2013, indicating an increase. According to the health profile of Bojonegoro Regency of 2018, out of 33,667 diarrhea cases reported, 31,010 or 92.11% of them were treated. This study aims to analyze the relationship between handwashing practice, use of latrine and SPAL (sewerage) with diarrhea incidents in Bojonegoro Incidents. This study used observational study design with cross-sectional approach. Samples in this study were 63 toddlers spread across 4 villages taken using proportional random sampling technique. The collection of primary data was performed by interviewing and observing mothers that had toddlers. Chi square test method was used to determine the relationship between variables examined, where diarrhea occurred in children under five if p < α (α margin of error = 0.05). The results of the study conducted from December 27, 2019 to January 31, 2020 showed that there was a significant relationship between handwashing habit and diarrhea incidents in toddlers, with p=0.000. There was no significant relationship between latrine condition and diarrhea in toddlers, with p=0.808. Furthermore, there was no significant relationship between SPAL condition and diarrhea incidents in toddlers, with p=0.085. There was a significant relationship between handwashing habits in mothers that had children under two with diarrhea incidents.